Reviewing the role of positive classroom climate in improving English as a foreign language students’ social interactions in the online classroom - Qiu, Fei (Frontiers in Psychology, 2022)
The teacher and learners are cooperatively involved in the creation of a positive climate in an L2 class. In the online language learning environment today, teachers can make the best use of technology, multi-media learning, and accessibility of learners to create a supportive and effective climate. In this productive climate, the teacher and learners can have multiple forms of social interaction which can improve language learners’ communicative skills. Not only can the teacher expect better learning outcomes, but s/he can also ensure students’ wholehearted attendance in, attention to, and participation in class activities. A positive class climate and the consequent better social interactions can also enhance learners’ affective well-being, for example, with a higher self-esteem, less anxiety, and overall better emotional health. Suggestions are made on how to help teachers create a positive climate in online L2 classes and pave the way for more effective social interactions between teacher and students and among students. There will be implications for L2 teachers, researchers, and trainers, especially in the post-pandemic era.